Promyelocytic Leukemia with No Retinoic Acid Receptor Alpha Abnormality but with RUNX1T1 Insertion to Chromosome 7q: A Classification and Management Dilemma - Kathleen Overholt; Terri L. Guinipero; Nyla A. Heerema; Michael R. Loken; Samir B. Kahwash (Case Reports in Hematology)
A case of acute promyelocytic leukemia (APL) with RUNX1T1 insertion to 7q is described and compared to reported cases of APL with negative retinoic acid receptor alpha (RARA) abnormality. In this report, we describe the case of a 2-year-old boy who presented with bone pain and was found to have pancytopenia. Bone marrow examination showed morphologic and immunophenotypic findings typical of APL, but conventional cytogenetics, fluorescence in situ hybridization (FISH), and real-time polymerase chain reaction (RT-PCR) showed no evidence of RARA rearrangements. The only cytogenetic abnormality found was a small insertion in 7q, and three copies of RUNX1T1. Gene sequencing results became available after initiating therapy but were not informative. We describe the rarity of such cases and discuss how the typical morphologic and immunophenotypic findings of APL, coupled with the definite absence of RARA rearrangement (by FISH and RT-PCR), present a diagnostic and classification dilemma, raising the possibility of an unknown alternative mechanism for the leukemogenesis and maturation arrest seen in other APL variants. The diagnostic challenges and urgent management issues this unusual case raises may justify including it, along with similar cases, in a separate subtype of acute myeloid leukemia (AML) in future classifications.